Gender, resistance and identity: jewish immigrants in Brazil - Blay, Eva Alterman (Tempo Social, 2009)
Jews came to Brazil "to stay for good" from the first half of the 16th century. Yet settling in Brazil has been an ongoing project throughout the five centuries of Jewish immigration. They frequently had to hide their Jewish condition and, from the 18th century onwards, overcome political-ideological persecutions in order to safeguard their own identity and fight for their citizenship. How have these demands and struggles affected the relationships between men and women and among Jewish families? So how have these relationships been organized among Jews? Were inequalities brought along with their luggage? Or were the relations based on male dominance of women incorporated by Jewish immigrants after they arrived in Brazil? Can we affirm that relationships between Jewish men and women were generally egalitarian?